Deconstructing psychotherapy - Parker, Ian (Sage, 1999)
Putting forward the latest arguments on the discursive and postmodern turn in psychotherapy, the contributors reflect on the role of psychotherapy in contemporary culture, and the project of therapy is opened up to critical attention.